Portrait of an Artist as Collaborator: An Interpretative Phenomenological Analysis of an Artist - Hocking, Ian (Frontiers in Psychology, 2019)
The subjective experience of being an artist was examined using interpretative phenomenological analysis (IPA), focusing on the perspective of the artist but interpreted by me, a psychologist, from the perspective of artistic collaborator. Building upon a literature that has hitherto focused on clinical, elderly, or vulnerable participants, I interpreted superordinate themes of Process (Constraint, Playfulness, Movement) and Identity (The Ill-Defined Artist, Becoming, Mixing Identities, Choosing an Identity, Calling, Collaboration and Outsider). These themes are broadly similar to the existing literature, but emphasise identity while de-emphasising self reflection and the need to become an ‘insider’.